Antroposentrisme Struktural: Kegagalan Visi Pembangunan dan Krisis Etika Lingkungan dalam Kebijakan Nomenklatur Jagung di Pulau Sumbawa - Sulaiman Sulaiman; Muhammad Sarjan (Pelantar Press, 2026)
This study critically assesses regional development policies on Sumbawa Island, particularly the PIJAR program (Cattle, Corn, and Seaweed) and the corn nomenclature, through the perspectives of environmental ethics and critical theory. Employing a mixed-method approach, the research integrates a spatial analysis of land cover changes in the Padolo River Basin during 2017-2024 with a policy text examination based on Jürgen Habermas's theory of the